Development of a Physics Experiment Guidebook Using a Smartphone Assisted by the Phyphox Application - Junita, Ode; Sanlan, Sahlan; Khusnani, Azmi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
The purpose of this study was to determine how to create, evaluate, and implement a physics experiment manual for damped oscillatory motion using a smartphone and the Phyphox application. This study took place at the Integrated Science Laboratory of IKIP Muhammadiyah Maumere and involved 20 students from the second and fourth semesters of the Physics Education Study Program during the 2022/2023 academic year. The methodology used in this research was Research and Development (R&D), which followed the ADDIE development model consisting of five main stages: Analysis, Design, Development, Implementation, and Evaluation. The tools used in this study were expert validation sheets and student response questionnaires. Quantitative descriptive analysis techniques were used to calculate the proportion of expert validation scores and student response questionnaire results. Specialists in materials evaluated the physics experiment manual and gave it a rating of 94%. Meanwhile, media professionals evaluated the same manual and rated it 95%. The combined feedback from both groups indicates that the physics experiment handbook is very eligible to use. According to the student response questionnaire, the average score obtained by the students was 87%, which falls under the category of "very interested." This indicates that the physics experiment manual is highly suitable for learning physics.